Fungiciders påverkan på kvävehalten i höstvete : hur påverkar användandet av fungicider utnyttjandet och inlagringen av kväve i höstvete? - Hermansson, Anna (SLU/Agrosystems (until 121231), 2011)
A common perception is that fungicide treatments increases yield, but that the nitrogen of the particular grain is diluted so that the overall removal of grain nitrogen from the field remains unchanged. The aim of this paper is to demonstrate that a healthy crop reduces the risk of nutrient loss from agricultural land. The results from genotype and plant protection trials often show constant nitrogen content in the grain, although the yield has been increased. Results from such experiments are therefore processed in order to confirm this and show that it is no statistically significant difference between the protein content (and also nitrogen content) in crops which have undergone fungicide treatment compared to crops which remained untreated. The trials processed have been carried out in the southernmost part of Sweden and are distinguished to concern winter wheat production. The explanation to the results is that a healthy crop is able to maintain the biological functions of the plant in a more efficient way than a crop damaged by a fungal infection. However, the significance of this is determined by several factors of which include: the size of existing or possible future fungal infections, the availability of nitrogen in the soil, variety between years in the form of rainfall, solar radiation, etc. How nitrogen uptake and accumulation in grain is affected by fungicide treatment is an important factor to be more considered when determining which plant protection actions, and to some extent other agronomic measures, that are to be carried out in crops in the future. Efficiency in the area means that you can achieve a reduction of the amount of nutrient losses to streams and seas, and that farmers may have increased probability to grow a profitable crop with increased quality. There is also much potential in improving the efficiency of fertilizer use.